Nature, the Monumental and Urban Technological Networks in Víctor Moreno’s Edificio España (2012) and La ciudad oculta (2018) - Larson, Susan (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
If we affirmatively answer Maria Kaika and Erik Swyngedouw’s invitation to think beyond the ’fetishization of the modern city’ as the pinnacle of human-centered progress and achievement in order to consider the urban as both a process of transformed nature and the metabolic and social transformation of nature through human labor, the city becomes a ‘hybrid of the natural and the cultural, the environmental and the social’ (Kaika and Syngedouw; 122). This essay argues that markedly different ways of imagining monumental public spaces and the relationship between nature and the city have arisen since the economic crisis of 2008 in Spain. Urban cultures create opportunities to imagine these new social, material and symbolic transformations and are exemplified in the documentary films of Víctor Moreno Edificio España (2012) and La ciudad oculta (2018). Considered together, the two films capture the scale, depth and three-dimensionality of spaces that are made up of both organic and non-organic material flows in ways that encourage us to question some of our basic assumptions about the urban.